Results from the International Halocarbons in Air Comparison Experiment (IHALACE) - Hall, Bradley D.; Engel, A.; Mühle, J.; Elkins, J. W.; Artuso, F.; Atlas, E.; Aydin, M.; Blake, D.; Brunke, E.-G.; Chiavarini, S.; Fraser, P. J.; Happell, J.; et al. (Atmospheric measurement techniques, 2014)
Abstract. The International Halocarbons in Air Comparison Experiment (IHALACE) was conducted to document relationships between calibration scales among various laboratories that measure atmospheric greenhouse and ozone depleting gases. This study included trace gases such as chlorofluorocarbons (CFCs), hydrochlorofluorocarbons (HCFCs), and hydrofluorocarbons (HFCs), as well as nitrous oxide, methane, sulfur hexafluoride, very short-lived halocompounds, and carbonyl sulfide. Many of these gases are present in the unpolluted atmosphere at pmol mol-1 (parts per trillion) or nmol mol-1 (parts per billion) levels. Six stainless steel cylinders containing natural and modified natural air samples were circulated among 19 laboratories. Results from this experiment reveal relatively good agreement (within a few percent) among commonly used calibration scales. Scale relationships for some gases, such as CFC-12 and CCl4, were found to be consistent with those derived from estimates of global mean mole fractions, while others, such as halon-1211 and CH3Br, revealed discrepancies. The transfer of calibration scales among laboratories was problematic in many cases, meaning that measurements tied to a particular scale may not, in fact, be compatible. Large scale transfer errors were observed for CH3CCl3 (10-100%) and CCl4 (2-30%), while much smaller scale transfer errors (< 1%) were observed for halon-1211, HCFC-22, and HCFC-142b. These results reveal substantial improvements in calibration over previous comparisons. However, there is room for improvement in communication and coordination of calibration activities with respect to the measurement of halogenated and related trace gases.
Gesehen am 29.10.2020